Spatio-temporal differences and simulation studies of the carbon budget from fisheries in the northern marine economic circle of China - Jia, Dai; Liu, Xinyu; Guan, Xin; Guo, Jinfei; Zhang, Shuqi; Li, Haozheng; Jin, Yiyang; Sun, Jun (Frontiers in Marine Science, 2024)
With the proposal of dual carbon goals, enhancing carbon sinks and reducing carbon emissions has become a critical issue. Fisheries, as a component of agriculture, possess the dual attributes of being a "carbon sink" (biological carbon fixation) and a "carbon source" (the carbon emissions from fishing vessels). Therefore, it is necessary to assess the carbon sink and carbon emission levels of fisheries. The northern marine enhance the carbon sink capacity and decrease the carbon emissions of fisheries in the northern marine economic circle.